The use of threshold concepts to support student learning through assessment – a case for renewing public trust in business education and qualifications. Issue 4 (7th June 2021) - Bajada, Christopher; Singh, Sonika; Jarvis, Walter; Trayler, Rowan
ABSTRACT: We focus on the pedagogical merit of introducing and assessing Thresholds Concepts (TCs) in the curriculum with a view to (inter alia) regain public confidence and trust in the legitimacy of business education and qualifications – especially since the 2007–2010 global recession. While the education literature foregrounds the role of higher education in preparing graduates for responsible practice, we claim there has been insufficient attention to the potential that TCs hold for renewed focus on knowledge and capabilities of graduates through the vehicle of assessment. The implications are profound. In this paper, we examine a case of how the application, and assessments in particular, of TCs in a first year quantitative business subject has impacted positively on student performance in that subject as well as in subsequent subjects of which those courses depend.